Matz, Adolph and Milton F. Usry. Cost Accounting. Sixth Edition. South Western Publishing Co. Mulyadi. Akuntansi Biaya. Edisi 3. Yogyakarta: BPFE. Undang-Undang Nomor 17 Tahun 2000 tentang Pajak Penghasilan. - Adang Sudjana (The Winners, 2004)
Article is a result of a “book research” and try to describe the implementation of UU No. 17 tahun 2000 in a company, especially a company tax profit, that is how the influences of  inflation and deflation if the supply scored based on Average Method or FIFO.  In condition the supply record by company using Perpetual and or Physiscal Inventory Method.